PERSEPSI KEADILAN KOMPENSASI TERHADAP KOMITMEN ORGANISASIONAL MELALUI KEPUASAN KERJA - Wilujeng Rahayu (Universitas muhammadiyah malang, 2012)
PERSEPSI KEADILAN KOMPENSASI TERHADAP KOMITMENORGANISASIONAL MELALUI KEPUASAN KERJAWilujeng RahayuPT. PG Rajawali I Unit I Krebet Baru Bululawang, MalangE-mail: Wilujeng_Rahayu24@yahoo.comABSTRACTFairness has an important relationship to the concept of commitment, but has only received littleattention in the Human Resources Management literature. Basic question about the relationship betweenfairness and organizational commitment are whether there is a variable between these to constructsor whether there is direct influence. Previous literature has revealed mixed results. LockeLuthan (1990) state that the relationship of fairness in the form of an award contingent and noncontingent on organizational commitment through job satisfaction. The goal of this research is to testand prove that perception of fairness compensation affect on organizational commitment through jobsatisfaction. The research was conducted at PT. PG Rajawali I Krebet Baru Bululawang, Malang.There the entire employee population is fixed and using random sampling techniques the study obtained358 respondents. Three variables are collected using questionnaires and interviews: the perceptionof compensation’s fairness, organizational commitment and job satisfaction. The data is analyzedusing path analysis and regression. The results show that perception of compensation fairnesshas a positive and significant impact on organizational commitment and a significant positive effecton job satisfaction. Job satisfaction has positive and significant impact on organizational commitment.Perception of compensation fairness has a stronger influence on organizational commitment ifthe relationship is direct rather than the indirect influence job satisfaction as a mediating variable.From the results of indirect influence perception of compensation fairness to the commitment throughsatisfaction can be interpreted that the employee reminds not imported level of job satisfaction, butemployees feel that fair compensation from the company will further enhance employee commitmentto the organization.Keywords: compensation fairness perceptions, job satisfaction, organizational commitment.